Landscaping an Ecuadorian neighborhood in Queens, NY - Gubitosi, Patricia; Puma, Christian; Narváez, Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Diaspora studies on migration communities have shown how these transnational groups appropriate the new space in the receptive country through a process of deterritorialization and reterritorialization. These processes involve a reinterpretation and reconceptualization of the linguistic relationship between the language of the diaspora group and those spoken in the new home. One of the most visible places where this contextual relation must be negotiated is in the public sphere, where language, culture and identity are inevitably interwoven (Blackwood, Lanza & Woldemariam, 2016). Using a multimodal approach and using both qualitative and quantitative methodologies, this article analyzes how an Ecuadorian-American community in Queens transformed the linguistic landscape of their surroundings to make it similar to what this community had in their home country.